PENGARUH TEKNOLOGI KEUANGAN DAN PENDAPATAN MASYARAKAT TERHADAP PERILAKU KONSUMSI KONSUMEN USAHA MIKRO SEKTOR MAKANAN MINUMAN DI SWK KECAMATAN KREMBANGAN KOTA SURABAYA - Afifahtus Syaleha; Arga Christian Sitohang (Nirta Learning Centre, 2026)
The development of financial technology in the digital era has brought significant changes to transaction patterns and consumer behavior. This study aims to analyze the influence of financial technology and consumer income on consumption behavior in the food and beverage MSME sector at the Culinary Tourism Center (SWK) in Krembangan District, Surabaya City. Using a quantitative approach and multiple linear regression analysis, primary data were obtained through questionnaires from 97 respondents selected using a purposive sampling technique. The results show that financial technology and consumer income have a positive and significant effect on consumption behavior, both simultaneously and partially. This finding confirms that increased use of digital financial services and increased income encourage higher consumption tendencies. This research is expected to contribute to MSMEs and local governments in formulating policies to improve digital financial literacy and strengthen wiser and more sustainable consumer behavior.